2020
DOI: 10.1111/jocs.15171
|View full text |Cite
|
Sign up to set email alerts
|

Bedside surgical ligation of the patent ductus arteriosus in very‐low‐birth‐weight premature infants: Limited upper ministernotomy as an alternative approach

Abstract: Background: Patent ductus arteriosus (PDA) is an important cause of morbidity and mortality, especially in very-low-birth-weight infants. The aim of the present study was to evaluate the outcomes of bedside surgical ligation of PDA via limited upper ministernotomy as an alternative approach to thoracotomy. Materials and Methods: A total of 23 low-birth-weight premature infants, who underwent bedside ligation of PDA in the neonatal intensive care unit between January 2017 and April 2020, were enrolled. The pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Many albeit small observational retrospective studies on bedside PDA surgery in ventilator-dependent preterm infants (range: 23-32 GA weeks; mean postnatal age 16-32 days on the day of surgery) have reported that there are no additional surgically associated complications. [120][121][122][123] The surgical approach applied is usually the posterolateral thoracotomy, but in a small retrospective study mini-sternotomy appeared to be associated with shorter postoperative mechanical ventilation and length of stay. 123 In a recent large multicenter retrospective study comparing PDA ligations in the operating room (OR) and the NICU, no differences in mortality or sepsis could be detected after correcting for differences in GA, besides an increased postoperative hemodynamic instability in the OR group.…”
Section: Surgical Ligation: Bedside or Operating Theater?mentioning
confidence: 99%
See 2 more Smart Citations
“…Many albeit small observational retrospective studies on bedside PDA surgery in ventilator-dependent preterm infants (range: 23-32 GA weeks; mean postnatal age 16-32 days on the day of surgery) have reported that there are no additional surgically associated complications. [120][121][122][123] The surgical approach applied is usually the posterolateral thoracotomy, but in a small retrospective study mini-sternotomy appeared to be associated with shorter postoperative mechanical ventilation and length of stay. 123 In a recent large multicenter retrospective study comparing PDA ligations in the operating room (OR) and the NICU, no differences in mortality or sepsis could be detected after correcting for differences in GA, besides an increased postoperative hemodynamic instability in the OR group.…”
Section: Surgical Ligation: Bedside or Operating Theater?mentioning
confidence: 99%
“…[120][121][122][123] The surgical approach applied is usually the posterolateral thoracotomy, but in a small retrospective study mini-sternotomy appeared to be associated with shorter postoperative mechanical ventilation and length of stay. 123 In a recent large multicenter retrospective study comparing PDA ligations in the operating room (OR) and the NICU, no differences in mortality or sepsis could be detected after correcting for differences in GA, besides an increased postoperative hemodynamic instability in the OR group. 124 Similar findings with no differences in mortality or complications after PDA ligation performed either in the OR or the NICU were presented in a 2-center retrospective cohort study from 2021, with a significantly earlier closure in the NICU group by 24 days.…”
Section: Surgical Ligation: Bedside or Operating Theater?mentioning
confidence: 99%
See 1 more Smart Citation